Cysteine biosynthesis in Saccharomyces cerevisiae: mutation that confers cystathionine beta-synthase deficiency. - Ono, B (1988)
The cys2-1 mutation of Saccharomyces cerevisiae was originally thought to confer cysteine dependence through a serine O-acetyltransferase deficiency. In this study, we show that cys2-1 strains lack not only serine O-acetyltransferase but also cystathionine beta-synthase. However, a prototrophic strain was found to be serine O-acetyltransferase deficient because of a mutation allelic to cys2-1. Moreover, revertants obtained from cys2-1 strains had serine O-acetyltransferase but not cystathionine beta-synthase, whereas transformants obtained by treating a cys2-1 strain with an S. cerevisiae genomic library had cystathionine beta-synthase but not serine O-acetyltransferase. From these observations, we conclude that cys2-1 (serine O-acetyltransferase deficiency) accompanies a very closely linked mutation that causes cystathionine beta-synthase deficiency and that these mutations together confer cysteine dependence. This newly identified mutation is named cys4-1. These results not only support our previous hypothesis that S. cerevisiae has two functional cysteine biosynthetic pathways but also reveal an interesting gene arrangement of the cysteine biosynthetic system.